Kulturelle forskelle, sociale netværk og regionalitet i vikingetidens arkæologi - Sindbæk, Søren M. (Hikuin, 2008)
Cultural difference, social networks and regionality in Viking-period archaeology By Søren M. Sindbæk This study surveys the wealth and diversity of archaeological material which has come to light in recent decades in Denmark and neighbouring lands. It shows that prominent cultural differences between regions can be identified in this area in the Viking Period. Interpreting these differences in terms of identities, communications and social networks, it is argued that the most significant factor in forming cultural differences was not tribal grouping, resulting from barriers to contact or deliberate separation, but the impact of the gravitational fields of the most significant recurrent communicative events in Viking-Age Scandinavia: regional assemblies or thing-moots. Such occasions, at which large groups of people met with peers of their region, gave rise to shared cultural norms that were reflected in aspects of material culture. No distinctive feature of material culture can be identified whose distribution coincides even roughly with the extent of the medieval Danish kingdom. This does not imply that a common kingdom did not exist; rather that the network holding it together was constituted differently from those which sustained its provinces. There was no common assembly for the entire kingdom and thus no series of focal events to support the dissemination of common culture. As a concept and a political dominion ‘Denmark’ existed in some form throughout the Viking Age. But for most people within Denmark it meant a relatively distant and faint association compared with those within the districts or ‘lands’ where people met regularly.